Development of SARS-COV therapeutics using quaternary protein mimetics - Neo, Tuan Ling (2010)
SARS-CoV, a novel virus belonging to group IV coronavirus, was discovered in association with cases of severe acute respiratory syndrome (SARS) in 2003. The spike (S) protein of SARS-CoV is responsible for receptor binding and membrane fusion. The MPER, the Trp-rich membrane proximal external region in the S protein, is both enigmatic and therapeutically important. It is absolutely conserved in members of CoV family and highly conserved in other RNA viruses such as HIV and Ebola. In HIV, MPER contains the epitope essential for broadly neutralizing antibodies, and MPER-derived peptides are potent inhibitors of viral entry. Structurally, S protein is trimeric and membrane-anchored as a transmembrane protein. Interestingly, MPER undergoes different structural states, from monomer, trimer and possibly hexamer during the fusion event. The self association and rearrangement of MPER in their quaternary states may provide important clues to the fusion event. My thesis focuses on understanding the physical states of MPER and their roles in the entry mechanism of SARS-CoV. Mutational and biophysical studies on MPER showed the importance of Trp in synchronization of SARS-CoV fusion event. My results support the importance of Trp in MPER function, both residually and positionally. The residual importance of Trp identity is due to the ‘indole ring’ effect, whereas positional importance reveals that increase in helicity may be the key conformational change in S protein-mediated fusion. Taken together, it is believed that the role of Trp in MPER is its contribution to the plasticity of the fusion protein structure, to take on different oligomeric intermediate quaternary structures to synchronize the fusion event. Quaternary protein mimetics of MPER were designed to mimic and to understand the different oligomeric intermediate states of MPER during fusion. The results support current hypothesis that MPER takes an active role to perturb the apposed membrane during fusion and provides a low energy path for continuous lipid flow, thus enabling fusion. This study sheds light on the possible mechanism of the fusion process, that may involve the S protein undergoing a series of intermediate states prior to fusion pore formation. The key lies with the Trp of MPER contributing flexibility to S protein structure to allow this series of conformational changes. Using the MPER protein mimetics, the conserved virus fusion mechanism was targeted for development of mutation resistant antivirals. We show that this strategy is promising and could provide potential antiviral candidates for SARS CoV.